Epic model: Effectiveness of waste bank website-based deposit applications - Nunuk Latifah; Shanti Ike Wardani; M. Nur Fu'ad (Trigin Publisher, 2023)
Waste banks are an alternative way of handling waste that can be converted into something of economic value. The process of managing Waste Bank deposits with a computerized system is expected to improve the performance of Waste Bank managers. Sutojayan District has been using a website-based waste bank management application since 2021 and has recorded 660 transactions with a total of 1529 users. However, until now these transactions have only been carried out by 2 villages, namely Pandanarum and Jingglong, out of 11 villages in Sutojayan District. The sample used was 100 respondents from application users who came from managers and customers, this study aims to determine the effectiveness of the web-based Waste Bank Savings Application using the EPIC Model, with four indicators namely empathy, persuasion, impact, and communication. From the results of the study it can be concluded that empathy, persuasion, impact, and individual benefits have a positive and significant effect on user satisfaction of 0.292; 0.390; 0.326; 0.885. This shows that the higher the empathy, persuasion, impact, and individual benefits, the higher the user satisfaction. Meanwhile, communication has a negative and insignificant effect on user satisfaction of -0.042, due to the manager's own internal management problems.%MCEPASTEBIN%